Ласточ...ка: роман / Маша Трауб - Трауб Маша (с/с Трауб(м), 2008)
Экземпляры: ф.16 (20220321) / Инвентарный номер: 62060 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Т 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44